Dialyzability of Oxycodone and Its Metabolites in Chronic Noncancer Pain Patients with End‐Stage Renal Disease. Issue 5 (2nd September 2016) - Samolsky Dekel, Boaz Gedaliahu; Donati, Gabriele; Vasarri, Alessio; Croci Chiocchini, Anna Laura; Gori, Alberto; Cavallari, Giuseppe; Di Nino, Gianfranco; Mercolini, Laura; Protti, Michele; Mandrioli, Roberto; Melotti, Rita Maria; La Manna, Gaetano
Abstract: Objectives: Opioids are the preferred analgesic drugs to treat severe chronic pain conditions among dialysis patients; however, knowledge about their dialyzability features is limited. Oxycodone is increasingly used for the treatment of chronic pain conditions as oral controlled release (CR) tablets; however, evidence about this drug and its metabolites' dialyzability is lacking. Methods: We assessed, during 4‐hour dialysis sessions, the effect of standard hemodialysis (HD) and online hemodiafiltration (HDF) methods on the plasma concentration of oxycodone and its metabolites in n = 20 chronic pain patients with end‐stage renal disease who were stably treated with oral CR oxycodone. Chromatographic techniques were used to evaluate the studied compounds' plasma concentrations at three different time points during dialysis. Results: Mean plasma concentrations of oxycodone and noroxycodone in the sample showed an overall reduction trend over time, but it was less enhanced for noroxycodone. Mean reduction in oxycodone and noroxycodone arterial concentrations was significant and higher with HDF (54% and 27%, respectively) than with HD (22% and 17%, respectively). Analysis of the regression of these compounds' clearance on their increasing arterial concentration showed a more stable and linear clearance prediction with HDF (roughly 85 mL/min); with HD, for increasing arterial concentration, clearance of oxycodone decreased while noroxycodone clearance increased. Discussion: While no oxymorphone or noroxymorphone metabolites were detected, limited dialyzability of oxycodone and noroxycodone was documented along with insignificant postdialysis pain increment. This evidence will contribute toward considerations as to the safety of the use of oxycodone in dialysis patients in the future.